2019
DOI: 10.3390/su11184964
|View full text |Cite
|
Sign up to set email alerts
|

Power Market Equilibrium under the Joint FIP-RPS Renewable Energy Incentive Mechanism in China

Abstract: In order to support the development of renewable energy, countries around the world have adopted certain renewable energy incentive mechanisms, including feed-in tariff (FIT) and renewable portfolio standard (RPS). Based on the official report concerning renewable energy consumption issued by the Chinese government in 2018, FIT is no longer an ideal renewable incentive mechanism for China. The increasing financial burden of renewable subsidies on the government has prompted a transition from FIT to a more mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…RPS stands for Renewable Portfolio Standard, which is a policy mechanism that requires electricity providers to produce or purchase a certain percentage of their power from renewable sources such as wind, solar, biomass, or geothermal energy. The goal of RPS is to increase the use of renewable energy and reduce reliance on fossil fuels, thereby reducing greenhouse gas emissions and mitigating the impacts of climate change (Cai et al, 2019; Kong et al, 2022; Kwon, 2018). FiT is a policy mechanism that provides financial incentives to renewable energy producers by guaranteeing a fixed price for every unit of electricity they feed into the grid (Jenner et al, 2013; Mu et al, 2021).…”
Section: Energy Transitions Policy Of South Koreamentioning
confidence: 99%
“…RPS stands for Renewable Portfolio Standard, which is a policy mechanism that requires electricity providers to produce or purchase a certain percentage of their power from renewable sources such as wind, solar, biomass, or geothermal energy. The goal of RPS is to increase the use of renewable energy and reduce reliance on fossil fuels, thereby reducing greenhouse gas emissions and mitigating the impacts of climate change (Cai et al, 2019; Kong et al, 2022; Kwon, 2018). FiT is a policy mechanism that provides financial incentives to renewable energy producers by guaranteeing a fixed price for every unit of electricity they feed into the grid (Jenner et al, 2013; Mu et al, 2021).…”
Section: Energy Transitions Policy Of South Koreamentioning
confidence: 99%
“…FIP introduces a certain degree of market competition on the basis of FIT, which is a transitional way of renewable energy power generation from full acquisition to full bidding, which can effectively control costs and guide the sustainable development of renewable energy [15]. South Korea experienced a drastic transformation from FIT to RPS in 2012, and most renewable energy technologies were constantly updated and increased [16].…”
Section: The Consumption Of Renewable Energy In the Worldmentioning
confidence: 99%
“…Jiang et al [20] comparatively analyzed the implementation of the FIT and RPS mechanisms, and reviewed, in detail, the effect of the RPS mechanism on the behavior of electricity market subjects. Cai et al [21] and Wang et al [22] identified the optimal combination ratio of the TIP-RPS joint mechanism, which is conducive to promoting the consumption of renewable energy and enhancing social welfare. Zhao et al [23] and Hao et al [24] comparatively analyzed the effects of RPS, FIT, and their combination on renewable energy.…”
Section: Rps Implementation Effectmentioning
confidence: 99%
“…q RPS = q use , q use ≥ q pro q pro , q use < q pro (21) where π s 2 represents the profits of power retailers selling nonbundled energy and C 2 represents the wholesale price of power retailers buying nonbundled energy. In addition to the purchase cost of conventional energy, the wholesale price also includes the cost of green certificates corresponding to conventional energy in the green certificate market, C 2 represents their power purchase cost, C TGC represents the cost of green certificates corresponding to conventional energy in the green certificate market, π RPS represents the cost of purchasing green certificates by power retailers, p RPS represents the price of green certificate, q RPS represents the quantity of green certificate purchased by the province, q use represents the quantity of green certificate required by power consumers, and q pro represents the quantity of RPS quota requirements.…”
Section: Profits Of Nonbundled Energymentioning
confidence: 99%